Medico-legal autopsy of abandoned foetuses and newborns in India. (June 2016) - Behera, C; Sikary, Asit Kumar; Krishna, Karthik; Garg, Aayushi; Chopra, Saurav; Gupta, SK
Foeticide and the abandonment of newborns are important, albeit frequently neglected, issues. Concealment of childbirth is often seen in the setting of unwanted pregnancy which has been recognised as one of the most important factors in both cases. This study highlights the medico-legal autopsy findings of 238 abandoned foetuses and newborns over a period of 17 years (1996–2012) from the region of South Delhi, India. There was no sex predilection. The majority of the cases were full term. Nearly 35% of the foetuses were still born, about 29% were live born and the remainder were non-viable. Among the live born, death by homicide was more common than a natural death and most were left by the roadside. The abandoning and killing of newborns needs urgent attention, and strict measures are needed to save thousands of innocent lives.